The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0220773
|View full text |Cite
|
Sign up to set email alerts
|

Population structuring of the invasive mosquito Aedes albopictus (Diptera: Culicidae) on a microgeographic scale

Abstract: Aedes albopictus is an invasive mosquito species that has spread globally and can transmit several arboviruses, including dengue, chikungunya and yellow fever. The species was first reported in Brazil in 1986 and since then has been found in 24 of the 27 Brazilian states, often in peri-urban environments close to highly urbanized areas. To date, population genetics of this important mosquito in areas in the city of São Paulo has not been investigated. In this study, we used 12 microsatellite loci to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
(99 reference statements)
0
10
1
1
Order By: Relevance
“…This could possibly be due to a sampling bias, but, taking into account fixation indices between populations (Table 1), it may rather be an indication of the highly restricted gene flow between populations. Average Fst in this case were higher than those observed between the populations from other invasion regions such as Europe, continental Africa (Kotsakiozi et al, 2017;Pichler et al, 2019), and Brazil (Multini et al, 2019).…”
Section: Tiger Mosquito Dispersal and Bottleneckscontrasting
confidence: 66%
“…This could possibly be due to a sampling bias, but, taking into account fixation indices between populations (Table 1), it may rather be an indication of the highly restricted gene flow between populations. Average Fst in this case were higher than those observed between the populations from other invasion regions such as Europe, continental Africa (Kotsakiozi et al, 2017;Pichler et al, 2019), and Brazil (Multini et al, 2019).…”
Section: Tiger Mosquito Dispersal and Bottleneckscontrasting
confidence: 66%
“…The availability of environmental resources is vital to sustaining populations of vector mosquito species. The availability of these resources varies greatly in urban environments driving vector mosquito population dynamics, presence, and abundance [5,16,44,45]. Our results showed that mosquito species were abundantly found breeding and dwelling in urban farms, although they varied greatly in the community composition and abundance.…”
Section: Discussionmentioning
confidence: 70%
“…However, as there are no geographic barriers, such as mountains, bodies of water, or a large canyon between the environments, our results indicated that the specimens represent a large, well-distributed population with a high overall genetic homogeneity. Previous studies carried out with mosquitoes from Brazil on a micro-geographic scale, suggest that native species exhibited weaker genetic structure while invasive species were shown to be more genetically structured and diverse 10,11,63,64 .…”
Section: Discussionmentioning
confidence: 95%